Considerando alterações climáticas na escolha de áreas para conservação de serpentes na região hidrográfica Tocantins-Araguaia - Pelegrini, Sóstenes José Souza (2020)
One of the most effective ways to preserve biodiversity in situ is through the creation of protected areas. The expansion of the network of protected areas is crucial for efforts to conserve biodiversity to be optimized in suitable areas. To this end, it is important that new areas are chosen with clear criteria - for example, high diversity and level of endemism. It is increasingly important to consider the current global climate changes, as there is evidence that many species change their current range in response to new climatic conditions. Here, we seek to indicate which are the best areas for the conservation of snakes in the Tocantins-Araguaia Hydrographic Region, an area of great biological importance, but also increasingly threatened by human activities. We considered two climate change scenarios, an optimistic and a pessimistic one (RCP 45 and RCP85) and generated ecological niche models for the entire snake community in the region. Finally, using the generated models, the network of existing conservation units and the percentage of native vegetation obtained through MAPBIOMAS, we point out the most climatically stable areas as the most suitable for the conservation of snakes in this basin. For this we use the Zonation software. In our results, we observed that most of these areas are concentrated south of the study region, coinciding with the largest current gap in protected areas in this basin.